(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
The use of the tracer 18F-fluoro-3’-deoxy-3’-L-fluorothymidine ([18F]FLT) in positron emission tomography (PET) has been shown to be an effective tool for assessing tumor aggressiveness and early response to therapy. In this study, we investigated the applicability of [18F]FLT/PET to study the antitumor and anti–lung metastatic effects of rosmarinic acid (RA) in highly invasive breast cancer. 4T1 mammary carcinoma cells were injected into the flank of female Balb/c mice. The animals were treated daily with RA until day 21 after the inoculation of tumor cells. [18F]FLT/PET imaging was used to evaluate the response of primary tumors and lung metastases to RA treatment. PET Images showed a decreased [18F]FLT uptake in the lungs of mice after RA treatment. The antitumor effect of RA appears to be related to the inhibition of cell migration, cell proliferation, and blood vessel formation in the primary tumor. Furthermore, the inflammatory response was modulated by RA, which reduced the accumulation of mast cells and neutrophils in the primary tumor and of macrophages in the lungs. In conclusion, [18F]FLT/PET demonstrates the antitumor and antimetastatic effects of RA in a 4T1 breast tumor model. Furthermore, the findings suggest that RA modulates tumor angiogenesis and inflammation, resulting in antitumor and antimetastatic effects in a 4T1 breast carcinoma model.